A ratiometric fluorescence and colorimetric dual-mode assay for H2O2 and xanthine based on Fe, N co-doped carbon dots. (September 2020) - Wang, Lizhi; Liu, Yang; Yang, Zhouping; Wang, Yanying; Rao, Hanbing; Yue, Guizhou; Wu, Caimei; Lu, Changfang; Wang, Xianxiang
Abstract: In this study, using diethylenetriaminepentaacetic acid (DPTA), diethylenetriamine (DETA) and Fe (NO3 )3 .9H2 O, Fe, N co-doped carbon dots (Fe, N-CDs) were successfully synthesized by a simple one-pot hydrothermal method. Fe, N-CDs possessed fluorescence and peroxidase-like properties. When H2 O2 was present, o-phenylenediamine (OPD) can be oxidized by Fe, N-CDs to oxidized phenylenediamine (oxOPD), and oxOPD further quenched the fluorescence of Fe, N-CDs because of inner filter effect. There were two peaks at 450 nm and 560 nm for the system of Fe, N-CDs and oxOPD. Results showed that the concentration of H2 O2 can not only affect the fluorescence intensity but also the color of the oxOPD. Considering that the xanthine oxidase can oxidize xanthine to produce H2 O2, thus, a ratiometric fluorescent and colorimetric dual-signal sensor for H2 O2 and xanthine was developed. This new method was demonstrated to have high sensitivity and excellent selectivity for determination of H2 O2 and xanthine. The detection limits (LOD) for H2 O2 and xanthine were 0.047 μM and 0.02 μM with a ratiometric fluorescence method, and were 0.05 μM and 0.023 μM with a colorimetric method, respectively. This dual-signal sensor was used successfully for xanthine detection in human serum and urine. Graphical abstract: A ratiometric fluorescent and colorimetric dual-signal sensor for H2 O2 and xanthine were developed based on prepared fluorescence and peroxidase-like Fe, N-CDs. Image 1 Highlights: A bifunctional nanomaterial with both fluorescence and peroxidase-like properties were prepared. A ratiometric fluorescent and colorimetric dual-signal sensor for H2 O2 and xanthine were developed. The dual-signal sensor was used successfully for xanthine detection in human serum and urine.